Optimalisasi Pengolahan Limbah Rumah Tangga Menggunakan Metode Takakura Di Desa Tamansari - Sofi Faiqotul Hikmah; Nur Anim Jauhariyah; Abdul Aziz; Muhammad faqih; Fajar Isnaini; Moh. Riza Pahlevi (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Waste is one of the problems that must be overcome in the community because if it is not managed properly it can pollute the surrounding environment. A lot of waste is produced by human activities in the household, this waste can be in the form of leftovers that are consumed by the community. Good waste management will provide benefits for humans and can provide great opportunities for people to become entrepreneurs. Entrepreneurial opportunities in this case can increase people's incomes, create creative industries and develop the creative economy. Socialization activities and training on optimizing household waste into compost using the takakura method so that household organic waste is beneficial for the community, especially PKK women in Tamansari Village, Tegalsari District, Banyuwangi Regency. Because they are able to provide information and apply appropriate technology "takakura" in everyday life at home. In addition, PKK women in Tamansari Village understand the importance of processing household waste so that they participate in reducing the amount of piles of garbage in TPS and reducing environmental pollution.